Reaksi Pasar Terhadap Peristiwa Kenaikan Harga Bahan Bakar Minyak (BBM) Di Bursa Efek Indonesia - Ni Putu Sri Puspita Dewi; Ni Gusti Putu Wirawati (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
This study aims to determine the market reaction to the September 3, 2022 fuel price hike on the Indonesia Stock Exchange with an event window of 7 days. The number of samples used was 52 consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX). The method of determining the sample used is the non-probability sampling method with purposive sampling technique. The model used to estimate the expected return is the mean adjusted model. The data analysis technique used is One Sample t-test and Paired Samples t-test. The results of this study indicate that there is no significant difference in the average abnormal return before and after the fuel price increase. Based on these results indicate that the capital market in Indonesia is in the form of an efficient semi-strong market in terms of information.